Взаимосвязь информационной и охранительной функций права - Антошина, Ирина Владимировна; Антошина, Ірина Володимирівна; Antoshina, Irina (Одеса : Юрид. л-ра, 2012)
The article deals with the concept of the determination of theoretical and practical interrelation protective and informational function of law, and also their legal nature, essence and features of their joint realization from point of their influence on public relations.
Антошина И. В. Взаимосвязь информационной и охранительной функций права / И. В. Антошина // Актуальні проблеми держави і права : зб. наук. пр. /редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 221-227.
Keywords: функция права; информационная функция права; охранительная функция права; правовое регулирование; правовые средства; функція права; інформаційна функція права; охоронна функція права; правове регулювання; правові засоби; function of law; informational function of law; protective function of law; legal adjusting; legal facilities